2021
DOI: 10.3389/fcell.2021.690796
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Chromatin Modifier KAT2A Activates MCT1 to Drive the Glycolytic Process and Tumor Progression in Renal Cell Carcinoma

Abstract: ObjectivesThis study aims to investigate the underlying mechanisms of KAT2A/MCT1 axis in renal cell carcinoma (RCC), providing potential therapeutic targets.MethodsWe obtained the expression data of KAT2A and MCT1 from The Cancer Genome Atlas Kidney Clear Cell Carcinoma (TCGA-KIRC) and International Cancer Genome Consortium (ICGC) databases. Differential analysis was conducted via the limma package. The CCK8 assay, soft agar assay, clone formation assay, and patients-derived organoid models were used to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…After a full analysis, twelve studies were considered to fit into the aim of assessing AZD3965 antitumor efficacy in vivo. Within those studies, two were performed using cell lines from small cell lung cancer [ 27 , 32 ], six used non-Hodgkin’s lymphoma cells [ 19 , 28 , 33 , 35 , 36 , 37 ], two used breast cancer cells [ 37 , 38 ], one used head and neck squamous cell carcinoma cells [ 39 ], one used lung squamous cell carcinoma cells [ 40 ], one used colorectal carcinoma cells [ 36 ] and one used renal cell carcinoma cells [ 41 ]. Studies reported administration of AZD3965 as monotherapy alone [ 19 , 27 , 35 , 36 , 37 , 38 , 41 ], or monotherapy and combined with either radiation (2Gy for 3 days) [ 32 ] or other pharmacological therapy—doxorubicin or rituximab [ 33 ], BAY-2243 [ 28 ], simvastatin [ 39 ] or JNJ-605 [ 40 ], all compared to vehicle control.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After a full analysis, twelve studies were considered to fit into the aim of assessing AZD3965 antitumor efficacy in vivo. Within those studies, two were performed using cell lines from small cell lung cancer [ 27 , 32 ], six used non-Hodgkin’s lymphoma cells [ 19 , 28 , 33 , 35 , 36 , 37 ], two used breast cancer cells [ 37 , 38 ], one used head and neck squamous cell carcinoma cells [ 39 ], one used lung squamous cell carcinoma cells [ 40 ], one used colorectal carcinoma cells [ 36 ] and one used renal cell carcinoma cells [ 41 ]. Studies reported administration of AZD3965 as monotherapy alone [ 19 , 27 , 35 , 36 , 37 , 38 , 41 ], or monotherapy and combined with either radiation (2Gy for 3 days) [ 32 ] or other pharmacological therapy—doxorubicin or rituximab [ 33 ], BAY-2243 [ 28 ], simvastatin [ 39 ] or JNJ-605 [ 40 ], all compared to vehicle control.…”
Section: Resultsmentioning
confidence: 99%
“…All studies used mouse models to test AZD3965. Regarding gender, two studies used male mice [ 27 , 41 ], one did not report gender [ 28 ], and the remaining used female mice. Animal age ranged from 4 to 14 weeks, although, on average, experiments were conducted in adult mice (over 8 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations